Integrating RNA-sequencing and network analysis to explore the mechanism of topical Pien Tze Huang treatment on diabetic wounds - Cao, Guang-Zhao; Tian, Liang-Liang; Hou, Jing-Yi; Zhang, Yi; Xu, He; Yang, Hong-Jun; Zhang, Jing-Jing (Frontiers in Pharmacology, 2024)
Introduction: Diabetic ulcers have become one of the major complications of diabetes mellitus (DM) and are a leading cause of death and disabling disease. However, current therapies are not effective enough to meet clinical needs. A traditional Chinese medicine (TCM) formula, Pien Tze Huang (PZH), is known as a medicine that is used to treat diabetic ulcers. Methods: In this study, PZH (0.05 g/cm2 and 0.15 g/cm2) and the positive drug-rhEGF were topically administered in a high-fat diet (HFD) and streptozotocin (STZ)-induced diabetic full-thickness incisional wounds, respectively. Wound healing was assessed by wound closure rate, two-photon microscope (SHG), staining with Hematoxylin and eosin (H&E), and Masson's trichrome (MTC). Then, RNA sequencing (RNA-seq) analysis, Enzyme-linked immunosorbent assay (ELISA), western blotting, and immunofluorescence (IF), network analysis, were performed. Results and discussion: The results showed that PZH significantly accelerated wound healing, as well as enhanced the expression of collagen. RNA-seq analysis showed that PZH has functions on various biological processes, one of the key biological processes is inflammatory response. Tlr9, Klrk1, Nod2, Tlr2, and Ifng were identified as vital targets and the NF-κB signaling pathway was identified as the vital pathway. Additionally, PZH profoundly reduced the levels of Cleaved caspase-3 and promoted the expression of CD31 and TGF-β1. Mechanically, PZH significantly decreased expression of NKG2-D, NOD2, and TLR2, and further inhibited the activation of downstream NF-κB signaling pathway and inhibited expression of inflammatory factors (IFN-γ and IL-1β). Importantly, we found that several active ingredients may play a significant role in diabetic wound healing, including Notoginsenoside R1, Deoxycorticosterone, Ursolic acid, and 4-Methoxyphenol. In summary, our study sheds light on the complicated mechanisms underlying the promising anti-diabetic wounds of PZH and provides the discovery of agents treating diabetic ulcers.